PERBANDINGAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN STUDENT TEAM ACHIEVMENT DIVISION DAN THINK PAIRAND SHARE PADA MATERI SISTEM EKSKRESI SECARA DARING KELAS VIII SMP NEGERI 4 PEMATANGSIANTAR TAHUN PELAJARAN 2020/2021 - Affandi, Ridwan; Saragih, Marlindoaman (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2022)
This study aims to determine the differences in student learning outcomes and the magnitude of the differences in student learning outcomes using the Student Team Achievement Division and Think Pair and Share learning models on the excretory system online in grade VIII of SMP Negeri 4 Pematangsiantar in the 2020/2021 academic year. The population was 187 students, consisting of 6 classes, and the sample was taken using Cluster Random Sampling, resulting in two classes: experimental class 1 (VIII-5) with 32 students and experimental class 2 (VIII-8) with 32 students. Experimental class 1 was treated using the Student Team Achievement Division learning model, and experimental class 2 was treated using the Think Pair and Share learning model. Data analysis was carried out by finding the mean (X̅ ), standard deviation (S), and hypothesis testing (t-test) at a significance level of α = 0.05. The research results obtained an average post-test score of 86.09 for experimental class 1 and 85.16 for experimental class 2, with a difference in learning outcomes of 0.93. The results of the hypothesis testing (t-test) obtained thitung (2.625) > ttabel (1.99) at a significance level of α = 0.05 and degrees of freedom (dk) = 62. Therefore, Ho is rejected and Ha is accepted, meaning there is a difference in student learning outcomes using the Student Team Achievement Division and Think Pair and Share learning models on the online excretory system material for class VIII of SMP Negeri 4 Pematangsiantar in the 2020/2021 academic year. It was concluded that there is a difference in student learning outcomes using the Student Team Achievement Division and Think Pair and Share learning models on the online excretory system material for class VIII of SMP Negeri 4 Pematangsiantar in the 2020/2021 academic year.